SRC Kinase-Mediated Tyrosine Phosphorylation of TUBB3 Regulates Its Stability and Mitotic Spindle Dynamics in Prostate Cancer Cells - Alan Alfano; Jin Xu; Xi Yang; Dhanraj Deshmukh; Yun Qiu (MDPI AG, 2022)
Tubulin is an integral part of the cytoskeleton and plays a pivotal role in cellular signaling, maintenance, and division. β-tubulin is also the molecular target for taxane compounds such as docetaxel (DTX) and cabazitaxel (CTX), both first-line treatments for several solid cancers. Increased expression of Class III β-tubulin (TUBB3), a primarily neural isoform of β-tubulin, correlates with taxane resistance and poor prognosis. Although tyrosine kinase c-Src has been implicated to phosphorylate β-tubulins during both hematopoietic and neural differentiation, the mechanisms by which Src modulates tubulins functions are still poorly understood. Here, we report, for the first time, that TUBB3 is phosphorylated at Tyrosine 340 (Y340) by c-SRC in prostate cancer cells. We also showed that Y340 phosphorylation regulates TUBB3 protein stability and subcellular localization. Furthermore, we demonstrated that inhibition of SRC kinase activity compromises spindle stability in mitotic cells, at least partly due to the lack of TUBB3 Y340 phosphorylation. Given the importance of TUBB3 as a clinical biomarker of poor prognosis and drug resistance, characterization of TUBB3 posttranslational regulation could potentially serve as new biomarkers for disease recurrence and/or treatment failure.